Empresa transnacional, regulação e tutela dos interesses transindividuais - Giannasi, Luciana Cristina (2023)
In modern society, marked by the technological revolution and the phenomenon of globalization, transindividual interests of relevance to society, such as the environment, have been put at risk, on a larger scale, due to the activities carried out by transindividual companies around the globe. Given this reality, this research seeks to analyze the issue of protecting transindividual interests at the international level, in view of the activities carried out by transnational companies and the consequent need for regulation, through international regulations, of the activities of these companies with a view to protecting the human rights considered in all their dimensions. Initially, we seek to discuss the affirmation of human rights in the international order, with emphasis on diffuse interests, classified as human rights of the third dimension. Next, the relationship between companies and human rights, the regulation of the activities of transnational corporations and other companies, with emphasis on the UN Guiding Principles on Business and Human Rights and their contribution to the preservation of human rights, embodied in the tripod Protect, Respect and Remedy. Then, a brief analysis of the characteristics of voluntary and binding regulations is carried out in order to address the central theme of this study, namely, the need to create an international treaty on human rights for companies. At this point, it analyzes the revival of discussions around the need to build binding regulations for companies on human rights and the advances in debates at the UN Human Rights Commission, making a cut in the criminal liability of transnational companies, provided for in the drafts of the legally binding instrument for transnational corporations and other companies that are the subject of discussion by the United Nations Intergovernmental Working Group on Transnational Corporations and Other Undertakings Relating to Human Rights – IGWG. The work has as a theoretical reference the authors John Ruggie and Zubizarreta, who have opposing views on the subject and made use of bibliographical and documental analysis, using the deductive method. In conclusion, it is necessary to recognize the need for a restructuring of the human rights protection system, understanding that, alongside states, transnational corporations can also act as violators of these rights, given their current position of power in the global scenario. Therefore, there is a need to consider assigning these corporations the obligation to preserve and protect human rights. In this regard, the existence of binding international regulations for companies regarding human rights can greatly contribute to the effective protection of diffuse and collective rights, as it will make the compliance with the established obligations mandatory, with the consequent imposition of sanctions in case of non-compliance.